Anomalous diffusion in artificial lipid bilayers - Coker, H (2018)
Diffusion is a process essential to life. The way diffusion processes occur at, and within, the cell membrane is of particular importance for cellular signalling, transport and cellular integrity. However, within cell membranes, diffusion of lipids and proteins has been shown to be ‘anomalous’. In such cases the molecules do not conform to basic Brownian motion and instead show slower diffusion over long timescales. The cell exploits this to tightly control the movement of key molecules including receptors. Although it has been hypothesised that this is due to the complex, crowded environment found within the membrane, the physical basis for anomalous diffusion is not yet fully understood and certainly is not well controlled in current membrane mimics. In the present work, artificial lipid bilayers were used to produce platforms in which to exhibit, control and study anomalous diffusive processes. A combination of fluorescence and optimised interferometric scattering microscopies, allowed careful study of this diffusive behaviour over biologically relevant length and timescales.